EFEKTIVITAS EDUKASI KESEHATAN BERBASIS KEPERAWATAN KOMUNITAS TERHADAP PENINGKATAN PERILAKU PENCEGAHAN DEMAM BERDARAH DENGUE: LITERATURE REVIEW - Elvina Rose Damayanti; Miftahul Falah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Dengue Hemorrhagic Fever (DHF) remains a significant public health problem in Indonesia and is closely related to prevention behaviors at the household and community levels. Health education delivered by community nurses has the potential to serve as a key strategy in improving knowledge, attitudes, and preventive behaviors related to DHF. This study aims to analyze the effectiveness of community-based nursing health education in improving DHF prevention behaviors. The method used was a systematic literature review guided by the PRISMA 2020 framework. Article searches were conducted in December 2025 through Google Scholar, Portal Garuda, and ScienceDirect using the keywords “dengue hemorrhagic fever,” “health education,” “community nursing,” “community,” and “prevention behavior.” Out of 4,285 identified articles, five studies met the inclusion criteria and were analyzed further. All included studies used quantitative designs with health education interventions in community settings and assessed changes in knowledge, attitudes, and DHF prevention behaviors. The synthesis results indicate that health education delivered through lectures, discussions, leaflets, and animated videos consistently improved knowledge, and most studies also reported improvements in preventive practices, including the 3M activities and water container management. This review concludes that community-based nursing health education is effective in enhancing DHF prevention behaviors and should be integrated continuously into dengue control programs at the primary healthcare level.